NURSING STUDENTS PERCEPTION TOWARDS CARING BEHAVIOR OF CLINICAL INSTRUCTOR: A LITERATURE REVIEW - Sri Yulian Hunowu; Fitri Arofiati (Universitas An Nuur, 2019)
Background: Important factors for student success are determined by the behavior of an instructor. Students understand that caring instructors clinic can make students more confident. Caring behavior is a behavior that always assists others holistically. The objective is to know the perception of the caring behavior of nursing students on the clinical instructor. Method: This literature review uses searches from the Google Scholar database, Science Direct, EBSCO. At the initial stage of the search with keywords: